2011
DOI: 10.1007/s12221-011-0932-4
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing characteristics of Nylon, cotton and N/C mixture fabrics with reactive-disperse dyes containing a sulphatoethylsulphone group

Abstract: The dyeing and color fastness properties of three reactive-disperse dyes containing a sulphatoethylsulphone group on Nylon, cotton and N/C mixture fabrics were examined. Reduction-clearing was more effective in removing the unfixed dyes than soaping since the reactive-disperse dye became hydrophobic during dyeing process. Nylon was dyed well with three reactive-disperse dyes at pH 5~8 and difference in chemical structure between dyes did not affect the final color strength of the dyed Nylon fiber, but their bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…14 Two of the studies 12,13 were performed in the absence of electrolyte and proprietary leveling agent, and generally syntan treatment did not improve the wash fastness of the dyeings. Kim et al 18 researched the dyeing characteristics of nylon, cotton and N/C (nylon/cotton) mixture fabrics with reactive-disperse dyes containing a sulfatoethylsulfone group and concluded that washing fastness and rubbing fastness of dyed nylon, cotton and N/C fabrics with the reactive-disperse dyes were excellent, while light fastness was moderate. Kim et al 19 (the same research team) also researched dyeing properties of nylon, polyethylene terephthalate (PET), and N/P (nylon/polyester) mixture fabric with reactive-disperse dyes having a sulfatoethylsulfone group and concluded that the reactive-disperse dyes were found to be adequate for the one-bath, one-step dyeing of N/P mixture fabric when applied at pH 5 and 120 ο .…”
Section: Introductionmentioning
confidence: 99%
“…14 Two of the studies 12,13 were performed in the absence of electrolyte and proprietary leveling agent, and generally syntan treatment did not improve the wash fastness of the dyeings. Kim et al 18 researched the dyeing characteristics of nylon, cotton and N/C (nylon/cotton) mixture fabrics with reactive-disperse dyes containing a sulfatoethylsulfone group and concluded that washing fastness and rubbing fastness of dyed nylon, cotton and N/C fabrics with the reactive-disperse dyes were excellent, while light fastness was moderate. Kim et al 19 (the same research team) also researched dyeing properties of nylon, polyethylene terephthalate (PET), and N/P (nylon/polyester) mixture fabric with reactive-disperse dyes having a sulfatoethylsulfone group and concluded that the reactive-disperse dyes were found to be adequate for the one-bath, one-step dyeing of N/P mixture fabric when applied at pH 5 and 120 ο .…”
Section: Introductionmentioning
confidence: 99%
“…Two-step dyeing process for blended fibers could be replaced with one-step dyeing by employing reactive-disperse dyes. Factors affecting the dyeing ability of reactive-disperse dyes on different types of fibers are the dye structure and dyeing conditions [9][10][11][12][13]. In our previous work, the reactive-disperse dye was synthesized by using aminophenyl-4-(-sulphatoethylsulphone) as a diazo component and N,N-diethyl-m-toluidine as a coupling agent aiming for dyeing on cotton, PLA and cotton/PLA blended fabrics [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the reactive polymeric dispersant SMA–ESA was synthesised by amidation reaction between ESA and SMA . A reactive nanoscale CB dispersion was prepared with SMA–ESA and the colouring performance of the fabrics was further investigated.…”
Section: Introductionmentioning
confidence: 99%